In vivo quantification of VCAM-1 expression in renal ischemia reperfusion injury using non-invasive magnetic resonance molecular imaging. - Akhtar, A; Schneider, J; Chapman, S; Jefferson, A; Digby, J; Mankia, K; Chen, Y; McAteer, M; Wood, K; Choudhury, R (Public Library of Science, 2010)
RATIONALE AND OBJECTIVE: Vascular cell adhesion molecule-1 (VCAM-1) is upregulated in ischemia reperfusion injury (IRI), persisting after restoration of blood flow. We hypothesized that microparticles of iron oxide targeting VCAM-1 (VCAM-MPIO) would depict "ischemic memory" and enable in vivo assessment of VCAM-1 expression. METHODOLOGY AND FINDINGS: Mice subject to unilateral, transient (30 minutes) renal ischemia and subsequent reperfusion received intravenous VCAM-MPIO (4.5 mg iron/kg body weight). Contrast agent bound rapidly (<30 minutes) in IRI-kidneys and appeared as intensely low signal areas by MRI in vivo. Automated segmentation and quantification yielded MPIO contrast volumes of 5991±354×10(6) µm(3) in IRI vs. 87±7×10(6) µm(3) in kidneys with no surgical intervention (P<0.001); 90±8×10(6) µm(3) in IRI kidneys exposed to control (IgG-MPIO) and 625±80×10(6) µm(3), in IRI kidneys pre-treated with a blocking dose of VCAM-1 antibody (P<0.001). In keeping with quantitative MRI data, VCAM-1 mRNA expression in IRI was 65-fold higher than in kidneys without surgical intervention (3.06±0.63 vs. 0.05±0.02, P<0.001). Indeed VCAM-1 mRNA expression and VCAM-MPIO contrast volume were highly correlated (R(2)=0.901, P<0.01), indicating that quantification of contrast volume reflected renal VCAM-1 transcription. Serial imaging showed VCAM-MPIO accumulation at target within 30 minutes, persisting for ≥90 minutes, while unbound VCAM-MPIO was cleared rapidly from blood, with sequestration by mac-3 positive Kupffer cells in the liver and monocyte/macrophages in the spleen. CONCLUSIONS: (1) VCAM-MPIO detected VCAM-1 expression and defined its 3-dimensional distribution, revealing "ischemic memory" in renal IRI; (2) automated volumetric quantification of VCAM-MPIO accurately reflected tissue levels of VCAM-1 mRNA; and (3) VCAM-MPIO bound rapidly to target with active sequestration of unbound MPIO in the liver and spleen.